Synthetic Biomarker Design by Using Analyte‐Responsive Acetaminophen. (4th April 2017) - Nishihara, Tatsuya; Inoue, Joe; Tabata, Sho; Murakami, Shinnosuke; Ishikawa, Takamasa; Saito, Natsumi; Fukuda, Shinji; Tomita, Masaru; Soga, Tomoyoshi
Abstract: The use of synthetic biomarkers is an emerging technique to improve disease diagnosis. Here, we report a novel design strategy that uses analyte‐responsive acetaminophen (APAP) to expand the catalogue of analytes available for synthetic biomarker development. As proof‐of‐concept, we designed hydrogen peroxide (H2 O2 )‐responsive APAP (HR‐APAP) and succeeded in H2 O2 detection with cellular and animal experiments. In fact, for blood samples following HR‐APAP injection, we demonstrated that the plasma concentration ratio [APAP+APAP conjugates]/[HR‐APAP] accurately reflects in vivo differences in H2 O2 levels. We anticipate that our practical methodology will be broadly useful for the preparation of various synthetic biomarkers. Abstract : In vivo detection of an analyte from blood : Analyte‐responsive acetaminophen (APAP) can be used to estimate disease‐associated analyte levels from an in vivo conversion index. As proof‐of‐concept, hydrogen peroxide‐responsive APAP (HR‐APAP) enabled in vivo H2 O2 analysis from a blood sample following HR‐APAP injection.